PENGARUH PEMBAYARAN DIVIDEN TERHADAP KUALITAS LABA - Dwi Anita Nur Fitriani; Muchamad Syafruddin (Diponegoro Journal of Accounting, 2015)
This study aims to examine the influence of dividend payment on earnings quality. Dividend payment divided into four features, they are dividen-paying status, the amount of dividend, the amount rise of dividend , and dividend persistence. Samples consist of 81 firms from manufacturing industry are listed in Indonesia Stock Exchange on January 1, 2008 until December 31, 2012. Multiple regression used to be analysis technique. The empirical result of this study show that dividend-paying status, the amount rise of dividend, and persistence dividend have positively and significant influenced on earning quality, although author do not find evidence that larger  dividend is an indicator of higher earning quality.